MENGEMBANGAN KEARIFAN LOKAL MASYARAKAT MAITARA SEBAGAI OBJEK WISATA UNGGULAN KOTA TIDORE KEPULAUAN - Abdurrahman Kader (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2019)
This study focused on describing and analyzing the local wisdom tourism potential of Maitara people and developed as a leading tourismobject. This study uses a qualitative descriptive approach using an interactive model data analysis technique. The results showed that the Maitara people are still inherited and maintained some local wisdom has the potential to become a tourismobject, such as making wooden boats, Cakalangsmoked fish, breadfruit crepe obstructions, Ito Oti se Hadola Oti and Salai Jin rituals. Therefore, the local government, village government, and Maitara people have been made various efforts to develop their local wisdom to sustainable and leading tourism object. Meanwhile, the efforts made were Maitara festival event, art studio, and village company (BUMDes) establish and develop.